Determination of ideal protein ratios in growing pullets - Soares, Letícia [UNESP]; César de Paula Dorigam, Juliano; da Silva Viana, Gabriel; Balbino Leme, Bruno [UNESP]; Quintino do Nascimento, Mariana [UNESP]; Kochenborger Fernandes, João Batista [UNESP]; Kazue Sakomura, Nilva [UNESP] (My University, 2022)
Three N balance trials were conducted to determine the ideal protein for growing pullets. In each trial, a total of 96 pullets (Hy-line W-36) were randomly assigned to 12 treatments with 8 individual replicates for the starter (14–28d), grower (56–70d), and developer (98–112d). A balanced basal diet (BD) was formulated to meet pullet requirements for all essential amino acids (EAA) and other nutrients. Eleven additional limiting diets were formulated with corn starch and to meet all pullet nutritional requirements, except for amino acids (AA). Crystalline AA were then added to each one of the 11 limiting diet to achieve the same concentration to BD, except for the AA under study, which was provided in a marginal deficiency of 30% relative to the other EAA. Collected data of N intake, excretion and retention obtained in each trial was used to estimate the dietary protein quality (b) and AA efficiency utilization (bc−1). The deletion of individual AAs was used to determine the ideal protein for pullets using Göttingen and Louvain approaches. The ideal protein by Göttingen approach was obtained by dividing the bc−1 from limiting diet Lys by the bc−1 value obtained from EAA under study. The ratio between the EAA requirements and Lys requirements provided the ideal protein by Louvain approach. The ideal protein determined by Göttingen approach were: Lys = 100%; Met + Cys = 76%, 85% and 83%, Trp = 17%, 22% and 21%, Thr = 76%, 66% and 69%, Arg = 102%, 108% and 107%, Val = 75%, 81% and 83%, Ile = 65%, 68% and 76%, Leu = 105%, 122% and 122%, Phe + Tyr = 115%, 123% and 129%, Gly + Ser = 85%, 130% and 111%, His = 35%, 35% and 35% from 14 to 28 days, 56–70 days and 98–112 days, respectively. The ideal protein determined by Louvain approach were: Lys = 100%, Met + Cys = 73%, 79% and 67%, Trp = 18%, 21% and 21%, Thr = 68%, 67% and 70%, Arg = 108%, 109% and 109%, Val = 77%, 79% and 85%, Ile = 70%, 74% and 79%, Leu = 113%, 119% and 130%, Phe + Tyr = 122%, 126% and 133%, Gly + Ser = 78%, 135% and 124%, His = 37%, 37% and 39% from 14 to 28 days, 56–70 days and 98–112 days, respectively. Although estimates from both approaches were quite similar Göttingen approach EAAs ratios relative to Lys were more consistent compared with literature.
Keywords: Efficiency of nitrogen utilization; Egg laying type pullets; Essential amino acids; Nitrogen balance